Energy landscape: Petroleum utilization prospects amid global energy transition dynamics - Saputra, Robby (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: Petroleum has played a critical role in supporting industrialization and global economic growth since the Industrial Revolution. It has not only been the foundation of many economies, particularly transportation and industry, but it remains so today. However, the environmental impacts of petroleum use have become a global concern, prompting a shift to renewable energy. Methods: This study uses a qualitative approach with literature review and descriptive analysis to examine the prospects for petroleum use in Indonesia in the energy transition. Data were obtained from academic journals, government reports, and environmental studies to illuminate patterns of petroleum use, renewable energy developments, and their impacts on energy security and future policies. Findings: Indonesia has large potential for renewable energy sources such as hydropower, geothermal energy, and bioenergy, but their utilization is still minimal. Around 90% of this renewable energy potential has not been utilized. For example, hydropower, geothermal energy, and bioenergy which are environmentally friendly and capable of producing significant energy have not been fully developed. The biggest challenge in the transition to renewable energy lies in changing public perception, as many people still rely on fossil fuels. In addition, the Indonesian government faces the task of building infrastructure that is evenly distributed throughout the country. Conclusion: A proactive and gradual approach is needed to engage the public in renewable energy development and to raise awareness of its long-term benefits. Reducing dependence on petroleum requires strong policies, investment in renewable infrastructure, and public participation in the energy transition process. Novelty/Originality of this article: Unlike previous studies that have focused primarily on energy security and policy frameworks, this study emphasizes the importance of public perception and infrastructure readiness in supporting a successful transition from fossil fuels to renewable energy.